REAKSI PASAR ATAS PENGUMUMAN DIVIDEN TUNAI(STUDI EMPIRIS PADA PERUSAHAAN LQ-45) - Dwi Saputra, Akhsani Lubis; Darsono, Darsono (Diponegoro Journal of Accounting, 2015)
This study to analyze market reaction to the announcement of cash dividends on listed companies LQ-45 from February and August 2014. With the event window for 31 days and 15 days the researchers tried to see if there is a difference of abnormal return before and after the ex-dividend date. The sampling technique used is purposive sampling and number of samples used is 45 from manufactur industries. This study uses secondary data including historical daily closing stock price, market index LQ-45 and the schedule of cash dividends. The analysis technique used isEvent Study Method. The result showed that abnormal return obtained by investors after the date of the announcement rated investors as a signal of bad (bad news) because investors believe stock prices will fall after the announcement. However, the market is no longer reacting above 7 days after the ex-dividend date.